Defective gene expression of the membrane complement inhibitor CD46 in patients with progressive immunoglobulin A nephropathy. Issue 4 (9th April 2018) - Coppo, Rosanna; Peruzzi, Licia; Loiacono, Elisa; Bergallo, Massimilano; Krutova, Alexandra; Russo, Maria Luisa; Cocchi, Enrico; Amore, Alessandro; Lundberg, Sigrid; Maixnerova, Dita; Tesar, Vladimir; Perkowska-Ptasińska, Agnieszka; et al.
Abstract: Background: Complement is thought to play a role in immunoglobulin A nephropathy (IgAN), though the activating mechanisms are unknown. This study focused on the gene expression of CD46 and CD55, two key molecules for regulating C3 convertase activity of lectin and alternative complement pathways at a cellular level. Methods: The transcriptional expression in peripheral white blood cells (WBCs) of CD46 and CD55 was investigated in 157 patients enrolled by the Validation of the Oxford Classification of IgAN group, looking for correlations with clinical and pathology features and estimated glomerular filtration rate (eGFR) modifications from renal biopsy to sampling. Patients had a previous median follow-up of 6.4 (interquartile range 2.8–10.7) years and were divided into progressors and non-progressors according to the median value of their velocity of loss of renal function per year (−0.41 mL/min/1.73 m 2 /year). Results: CD46 and CD55 messenger RNA (mRNA) expression in WBCs was not correlated with eGFR values or proteinuria at sampling. CD46 mRNA was significantly correlated with eGFR decline rate as a continuous outcome variable (P = 0.014). A significant difference was found in CD46 gene expression between progressors and non-progressors (P = 0.013). CD46 and CD55 mRNA levels were significantly correlated (P < 0.01), although no difference between progressors and non-progressors was found for CD55 mRNA values. The prediction of progression was increased when CD46 and CD55 mRNA expressions were added to clinical data at renal biopsy (eGFR, proteinuria and mean arterial blood pressure) and Oxford MEST-C (mesangial hypercellularity, endocapillary hypercellularity, segmental glomerulosclerosis, tubular atrophy/interstitial fibrosis, presence of any crescents) score. Conclusions: Patients with progressive IgAN showed lower expression of mRNA encoding for the complement inhibitory protein CD46, which may implicate a defective regulation of C3 convertase with uncontrolled complement activation.